Sulfur Compounds in Regulation of Stomatal Movement - Ren, Zirong; Wang, Ru-Yuan; Huang, Xin-Yuan; Wang, Yin (Frontiers in Plant Science, 2022)
Sulfur, widely present in the soil and atmosphere, is one of the essential elements for plants. Sulfate is a dominant form of sulfur in soils taken up by plant roots. In addition to the assimilation into sulfur compounds essential for plant growth and development, it has been reported recently that sulfate as well as other sulfur containing compounds can also induce stomatal movement. Here, we first summarized the uptake and transport of sulfate and atmospheric sulfur, including H2O and SO2, and then, focused on the effects of inorganic and organic sulfur on stomatal movement. We concluded all the transporters for different sulfur compounds, and compared the expression level of those transporters in guard cells and mesophyll cells. The relationship between abscisic acid and sulfur compounds in regulation of stomatal movement were also discussed.